Multiplier Accounting of Indian Mining Industry: The Application - Hussain A.; Karmakar N.C. (My University, 2025)
In the previous paper (Hussain and Karmakar in Inst Eng India Ser, 2014. doi:10.1007/s40033-014-0058-0), the concepts of input–output transaction matrix and multiplier were explained in detail. Input–output multipliers are indicators used for predicting the total impact on an economy due to changes in its industrial demand and output which is calculated using transaction matrix. The aim of this paper is to present an application of the concepts with respect to the mining industry, showing progress in different sectors of mining with time and explaining different outcomes from the results obtained. The analysis shows that a few mineral industries saw a significant growth in their multiplier values over the years. © 2016, The Institution of Engineers (India).